Analysis of Student's Geometry Thinking Ability Based on Van Hiele's Theory - Nia Kania; Sudianto Sudianto; Hani Hanipah (Universitas Sebelas Maret, 2022)
The purpose of this study was to analyze students' geometric thinking skills in solving geometric problems based on Van Hiele's thinking stages. This research is a qualitative research. The subjects of this study were students of class XII MIPA 2 SMA Negeri Tomo, totaling 29 students. With purposive sampling obtained 6 research subjects representing the stages of thinking Van Hiele, data collection methods with test questions and interviews. Analysis of research data is data collection, data reduction, data presentation, and drawing conclusions. The results of the study are: no student can reach the rigor stage